Phase transition and negative thermal expansion in orthorhombic Dy2W3O12. Issue 98 (10th October 2016) - Cao, Weigang; Li, Qiang; Lin, Kun; Liu, Zhanning; Deng, Jinxia; Chen, Jun; Xing, Xianran
Abstract : Orthorhombic Dy2 W3 O12 shows NTE (−2.6 × 10 −5 °C −1 ) in the temperature range of 150–500 °C. So far, this value is the largest coefficient of negative thermal expansion in the A2 W3 O12 family (A = rare earth element). Abstract : New materials with suitable negative thermal expansion (NTE) are much desired to control thermal expansion in solids. In the present study, we determined the phase transition temperature of Dy2 W3 O12 from the monoclinic phase to the orthorhombic phase at 996 °C. The orthorhombic phase could be retained by quenching, and further high temperature XRD and synchrotron radiation X-ray powder diffraction (SXRD) experiments revealed that Dy2 W3 O12 shows NTE (−2.6 × 10 −5 °C −1 ) in the temperature range of 150–500 °C, which is the largest negative thermal expansion in the A2 W3 O12 family (A = rare earth element). A possible NTE mechanism and enhanced NTE were elucidated by the transverse thermal motion of the bridge oxygen in A–O–W linkages accompanied by distortion of the polyhedra with large Dy 3+ on the A site.